A cohort study comparing cardiovascular risk factors in rural Māori, urban Māori and non-Māori communities in New Zealand. Issue 3 (8th June 2012) - Cameron, Vicky A; Faatoese, Allamanda F; Gillies, Matea W; Robertson, Paul J; Huria, Tania M; Doughty, Rob N; Whalley, Gillian A; Richards, Mark A; Troughton, Richard W; Tikao-Mason, Karen N; Wells, Elisabeth J; Sheerin, Ian G; et al.
Abstract : Objectives: To understand health disparities in cardiovascular disease (CVD) in the indigenous Māori of New Zealand, diagnosed and undiagnosed CVD risk factors were compared in rural Māori in an area remote from health services with urban Māori and non-Māori in a city well served with health services. Design: Prospective cohort study. Setting: Hauora Manawa is a cohort study of diagnosed and previously undiagnosed CVD, diabetes and risk factors, based on random selection from electoral rolls of the rural Wairoa District and Christchurch City, New Zealand. Participants: Screening clinics were attended by 252 rural Māori, 243 urban Māori and 256 urban non-Māori, aged 20–64 years. Main outcome measures: The study documented personal and family medical history, blood pressure, anthropometrics, fasting lipids, insulin, glucose, HbA1c and urate to identify risk factors in common and those that differ among the three communities. Results: Mean age (SD) was 45.7 (11.5) versus 42.6 (11.2) versus 43.6 (11.5) years in rural Māori, urban Māori and non-Māori, respectively. Age-adjusted rates of diagnosed cardiac disease were not significantly different across the cohorts (7.5% vs 5.8% vs 2.8%, p=0.073). However, rural Māori had significantly higher levels of type-2 diabetes (10.7% vs 3.7% vs 2.4%, p<0.001), diagnosed hypertension (25.0% vs 14.9% vs 10.7%, p<0.001), treated dyslipidaemia (15.7% vs 7.1% vs 2.8%, p<0.001), current smoking (42.8% vs 30.5% vs 15.2%, p<0.001) and age-adjusted body mass index (30.7 (7.3) vs 29.1 (6.4) vs 26.1 (4.5) kg/m 2, p<0.001). Similarly high rates of previously undocumented elevated blood pressure (22.2% vs 23.5% vs 17.6%, p=0.235) and high cholesterol (42.1% vs 54.3% vs 42.2%, p=0.008) were observed across all cohorts. Conclusions: Supporting integrated rural healthcare to provide screening and management of CVD risk factors would reduce health disparities in this indigenous population.